Using language and culture material in ukrainian folklore classes - Zadorozhnya, L. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2020)
The methodical techniques and the methods of using language and culture material when teaching Ukrainian folklore are determined in the article. Ukrainian proverbs, sayings, songs, which reflect the vision of the Ukrainian people of female beauty, are language and culture material in this instance. The topicality of the research is caused by the extensive use of folkloric material in all modern languages with a didactic purpose and necessity of research in the ethnolinguoculturological aspect of language units that designate national and cultural stereotypes. The folklore of any nation belongs to the eternal phenomena; it is impossible to imagine the existence of a nation without it. National culture and specific features of mentality become known through folklore. Folklore helps to recreate the traits of any particular people, the development of ideas about different things. The use of proverbs in speech is an important indicator of language proficiency level. Working with proverbs and sayings helps to develop skills of speech activity. The studying of proverbs and sayings expands the students’ knowledge about language, form their aesthetic taste, desire to perfect their vocabulary. It improves speech culture, speaking skills, readiness for debating in Ukrainian. The increased use of proverbs enriches the spoken and written language. The use of proverbs adds originality, expressiveness, individuality, imagery and aphoristic nature to a person’s speech. Learning proverbs or sayings, students translate them into their language, comprehend and search for similar ones in their language. Discussing and comparing Ukrainian proverbs and sayings with proverbs and sayings in their native language, students develop skills in speaking, reading, and writing. Perspectives of further research are studies of the features of teaching language and culture material to foreign philological students and further development of new teaching material for the course “Ukrainian folklore”.